Complete genome sequence of two novel Chinese virulent porcine reproductive and respiratory syndrome virus variants - Zhou, Zhi; Li, Xiangdong; Liu, Qi; Hu, Dongmei; Yue, Xiaojuan; Ni, Jianqiang; Yu, Xiuling; Zhai, Xinyan; Galliher-Beckley, Amy; Chen, Nanhua; Shi, Jishu N.; Tian, Kegong (My University, 2012)
A highly pathogenic strain of porcine reproductive and respiratory syndrome virus (PRRSV), characterized by a discontinuous 30-amino-acid deletion in its Nsp2-coding region, has been emerging in China since 2006. Here, we report the complete genomic sequence of two novel Chinese virulent PRRSV variants with additional NSP2-gene deletions, which will help us understand the molecular and evolutionary characteristics of PRRSV in Asia.
Keywords: Porcine reproductive and respiratory syndrome virus; Complete genome sequence; PRRSV; China